ANALISIS STRUCTURE, CONDUCT, DAN PERFORMANCE (SCP) INDUSTRI TEKSTIL DAN PRODUK TEKSTIL DI INDONESIA - Rezeki Angriani Siregar; Irsyad Lubis (Departemen Ekonomi Pembangunan USU, 2015)
The purpose of this study is to analyze structure, conduct, and performance of textile and garment industry in Indonesia with an annual 2006-2013 and data totaled 2 subsector in TPT industry in group ISIC code 2 digit. The type data at this research is secondary data which is collection from Badan Pusat Statistik (BPS) and literature related to this study. The method used Structure-Conduct-Performance (SCP) analysis and panel data analysis with Random Effect Model (REM). The data process by using software Microsoft Office Excel 7 and E-views 7 program.The result of SCP analysis found that the industrial structure of TPT industry in Indonesia is a loose oligopoly structure, with an average value of CR4 of 12,02 percent. The average value MES of 4,98 percent show an opportunity for the entry of the new firms in to industry. Analysis of conduct of TPT industry seen strategy of product, price, and promotion. In terms of performance can be seen from PCM, efficiency (XEF), and growth.The estimation result of panel data indicate that by parsial, variable that have the greatest effect and significant performance increased (PCM) is efficiency (XEF). CR4 variable no significant negative effect to PCM. While MES and growth no significant positive effect to PCM of TPT industry in Indonesia. And by simultan, CR4, MES, efficiency (XEF), and growth have effect on PCM.Keywords: Structure-Conduct-Performance (SCP), Concentration Ratio (CR4), Minimum Efficiency of Scale (MES), Efficiency (XEF), Growth Output, Price Cost Margin (PCM)